Optimization of Glass Microelectrode Properties by Response Surface Methodology - Kisaalita, William S.; Skeen, Rodney S.; Van Wie, Bernard J.; Barnes, Charles D.; Fung, Simon J. (Journal of neuroscience methods, 1991)
Glass microelectrodes filled with electrolyte solutions are standard tools for electrophysiological studies. However, for any given application, there are limitations to the properties of the microelectrode, such as impedance and shank length, that can yield satisfactory results. The trial and error approach in pulling electrodes with the desired properties can be time consuming. The use of a response surface procedure which allows the experimenter to change more than one factor at a time and therefore determine the desired puller condition more efficiently is demonstrated. Also, design improvements for the World Precision Instrument, Model PUL-1, Microelectrode puller, used in this study are suggested.